La GIZC à l’épreuve du terrain : premiers enseignements d’une expérience française - Catherine Meur-Ferec (Éditions en environnement VertigO, 2009)
Foundation of Integrated Coastal Zones Management (ICZM) can be summed up to the application on the coast of the principles of sustainable development. The European recommendation of May 30th, 2002, asking every Member state to establish its national strategy, fell due in 2006. So ICZM is of a strong current events today. Beyond the official strategy, ICZM raises numerous questions on the real incidence of this new approach of the coast. Answers to a national call " for a well-balanced development of the littoral territories by a ICZM ", launched in 2005 by the State towards the stakeholders of the coast, offer the opportunity to study the GIZC " in action ". The analysis of the 49 projects allows to draw temporarily the characteristics, the brakes and the tracks dealing with the process of implementation of ICZM today in France.